KEEFEKTIFAN COMPUTATIONAL THINGKING (CT) DAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KREATIVITAS SISWA TERHADAP PENYELESAIAN SOAL-SOAL CERITA MATERI PERBANDINGAN (SKALA PADA PETA) DI SEKOLAH DASAR - Sri Kadarwati; Suparman Suparman; Kasni Astutik (Universitas Muhammadiyah Semarang, 2020)
This study aims to determine whether there is an influence of creativity on student learning outcomes in learning Computational Thingking (CT) and learning with Problem Based Learning (PBL) on solving comparative story material questions (scale on maps) in elementary schools, and to find out whether there is a difference between the acquisition of learning outcomes using Computational Thingking (CT) learning and learning with Problem Based Learning (PBL). This research is a true experimental study using Control group pre-test post test design. The population is Sambiroto 02 Public Elementary School students as many as 75 students in the 2018/2019 school year. The results of the study, namely the average learning outcomes in group E1 (learning with Computational Thinking) 80, with the lowest score of 78 and the highest value of 100. The average learning outcomes in group E2 (learning with Problem Based Learning) 87, with the lowest value of 82 and the highest value of 100 Average learning outcomes in the Control group (Expository learning) 66, with the lowest value 62 and the highest value 76. The effect of creativity on student learning outcomes in the E1 group was 79.95%. The effect of creativity on student learning outcomes in group E2 was 88.12%.